PENGARUH LINGKUNGAN KERJA, DISIPLIN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA PT OSI ELECTRONICS - Riantiana Pardede,; Putu Hari Kurniawan, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
Human resources are essential to achieving the objectives of a company by having good performance. Performance is the result of the work by each individual or group in the form of quality and quantity in carrying out its duties in accordance with the responsibilities that have been determined. This research aims to know and analyze the impact of work environment, work discipline and work stress on the performance of employees at Pt Osi Electronics. Sampling techniques are conducted based on the formula Slovin by using the probability sampling method with simple random sampling. The data collection techniques used in this research are using polls that use 131 employees as samples of research. The analytical techniques used are multiple regression analyses. The results of this study proved that the work environment has been partially influential in the performance of employees with significance levels 0.000 < 0.05. Working disciplines partially significantly affect employee performance with a significance rate of 0.004 < 0.05. Work stress is partially no effect on employee performance with significance levels 0131 > 0.05. Working environment, work discipline and work stress simultaneously affect employee performance with significance levels 0.000 < 0.005